A abordagem do conteúdo de genética: uma análise de livros didáticos aprovados pelo PNLD 2021 - Del Rio, Luana Lima (Universidade Federal de São Carlos, 2023)
The present work aims to analyze how high school textbooks, approved in the National Textbook and Learning Material Program (PNLD) 2021, approach Genetics content and all its complexity. The teaching of Genetics, as well as that of Biology in general, to be effective and meaningful, must be based on the assumptions of STS education (Science, Technology, and Society) and the progressive education of Paulo Freire, to form critical citizens and aware of their realities, capable of transforming them. Genetics is a complex area in continuous development, difficult to understand and with many challenges in its teaching, the main one being the prioritization of the textbook as a teaching tool, wich has the potential for the formation of critical citizens, if aligned with critical and emancipatory perspectives of education. Therefore, sought to analyze how this area is being approached in eight textbooks distributed to the public school system by the PNLD, using qualitative research and document analysis methodologies, based on the aspects: I) approach to genetics and relation with other areas of Biology and Natural Sciences; II) Approach of the history of science; III) Language complexity and explanation of concepts, IV) Approaching content to students' lives and V) Approach of New Biology and Genetic Counseling. From these aspects, it was possible to observe that there is a concern to make textbooks less content-oriented and more connected with the development of student's critical thinking, making teaching go against STS education and emancipatory education, despite still needing constant attention and updating.
The approach to genetics content: an analysis of textbooks approved by the PNLD 2021
Keywords: Genética; Ensino de genética; Livros didáticos; Genetics; Genetics teaching; Textbooks; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM